Chief Editor's Voice - Jha, Ashok Kumar (Dristikon: A Multidisciplinary Journal, 2026)
The Research Management Cell (RMC) of Mahendra Multiple Campus takes immense pleasure in announcing again the successful publication of the annual multidisciplinary peer-reviewed journal Dristikon, vol. 16(1) in the year 2026. This issue has undergone a rigorous editorial and peer-review process in accordance with the standards and guidelines prescribed by UGC, Nepal and international academic publishing practices. The peer-review system is intended to ensure the acceptance of authentic and well-structured scholarly articles, the improvement of manuscripts requiring revision, and the rejection of unsuitable submissions. The editorial board carefully evaluated and approved all reviewer recommendations. Furthermore, each manuscript submitted for publication was subjected to a comprehensive double-blind peer-review process to maintain academic quality and integrity. The main objective of a research article is to communicate new knowledge supported by credible evidence, and therefore every statement made by the authors must be critically assessed before publication. In recent times,